Automated glycan assembly of arabinomannan oligosaccharides from Mycobacterium tuberculosis - Pardo-Vargas, Alonso; Bharate, Priya; Delbianco, Martina; Seeberger, Peter H. (Beilstein Journal of Organic Chemistry, 2019)
Arabinomannan (AM) polysaccharides are clinical biomarkers for Mycobacterium tuberculosis (MTB) infections due to their roles in the interaction with host cells and interference with macrophage activation. Collections of defined AM oligosaccharides can help to improve the understanding of these polysaccharides and the development of novel therapeutical and diagnostic agents. Automated glycan assembly (AGA) was employed to prepare the core structure of AM from MTB, containing α-(1,6)-Man, α-(1,5)-Ara, and α-(1,2)-Man linkages. The introduction of a capping step after each glycosylation and further optimized reaction conditions allowed for the synthesis of a series of oligosaccharides, ranging from hexa- to branched dodecasaccharides.
Keywords: arabinomannan; automated glycan assembly; capping

Global Tuberculosis Report 2018 (World Health Organization, 2018)

(untitled) - Angala, S. k.; Palčeková, Z.; Belardinelli, J. M.; Jackson, M. (Nat. Chem. Biol., 2018)

(untitled) - Besra, G. S.; Khoo, K.-H.; McNeil, M. R.; Dell, A.; Morris, H. R.; Brennan, P. J. (Biochemistry, 1995)

(untitled) - Shi, L.; Berg, S.; Lee, A.; Spencer, J. S.; Zhang, J.; Vissa, V.; McNeil, M. R.; Khoo, K.-H.; Chatterjee, D. (J. Biol. Chem., 2006)

(untitled) - Briken, V.; Porcelli, S. A.; Besra, G. S.; Kremer, L. (Mol. Microbiol., 2004)

(untitled) - Owens, N. A.; Young, C. C.; Laurentius, L. B.; De, P.; Chatterjee, D.; Porter, M. D. (Anal. Chim. Acta, 2019)

(untitled) - Sigal, G. B.; Pinter, A.; Lowary, T. L.; Kawasaki, M.; Li, A.; Mathew, A.; Tsionsky, M.; Zheng, R. B.; Plisova, T.; Shen, K.; Katsuragi, K.; Choudhary, A.; et al. (J. Clin. Microbiol., 2018)

(untitled) - Chang, Y.; Meng, X.; Li, Y.; Liang, J.; Li, T.; Meng, D.; Zhu, T.; Yu, P. (MedChemComm, 2019)

(untitled) - Amin, A. G.; De, P.; Spencer, J. S.; Brennan, P. J.; Daum, J.; Andre, B. G.; Joe, M.; Bai, Y.; Laurentius, L.; Porter, M. D.; Honnen, W. J.; Choudhary, A.; et al. (Tuberculosis, 2018)

(untitled) - Choudhary, A.; Patel, D.; Honnen, W.; Lai, Z.; Prattipati, R. S.; Zheng, R. B.; Hsueh, Y.-C.; Gennaro, M. L.; Lardizabal, A.; Restrepo, B. I.; Garcia-Viveros, M.; Joe, M.; et al. (J. Immunol., 2018)

(untitled) - Counoupas, C.; Pinto, R.; Nagalingam, G.; Britton, W. J.; Triccas, J. A. (Vaccine, 2018)

(untitled) - Lindenstrøm, T.; Agger, E. M.; Korsholm, K. S.; Darrah, P. A.; Aagaard, C.; Seder, R. A.; Rosenkrands, I.; Andersen, P. (J. Immunol., 2009)

(untitled) - Lawn, S. D.; Gupta-Wright, A. (Trans. R. Soc. Trop. Med. Hyg., 2016)

(untitled) - Zheng, R. B.; Jégouzo, S. A. F.; Joe, M.; Bai, Y.; Tran, H.-A.; Shen, K.; Saupe, J.; Xia, L.; Ahmed, M. F.; Liu, Y.-H.; Patil, P. S.; Tripathi, A.; et al. (ACS Chem. Biol., 2017)

(untitled) - Broger, T.; Sossen, B.; du Toit, E.; Kerkhoff, A. D.; Schutz, C.; Ivanova Reipold, E.; Ward, A.; Barr, D. A.; Macé, A.; Trollip, A.; Burton, R.; Ongarello, S.; et al. (Lancet Infect. Dis., 2019)

(untitled) - Maiti, K.; Syal, K.; Chatterji, D.; Jayaraman, N. (ChemBioChem, 2017)

(untitled) - Sahloul, K.; Lowary, T. L. (J. Org. Chem., 2015)

(untitled) - Hölemann, A.; Stocker, B. L.; Seeberger, P. H. (J. Org. Chem., 2006)

(untitled) - Wu, Y.; Xiong, D.-C.; Chen, S.-C.; Wang, Y.-S.; Ye, X.-S. (Nat. Commun., 2017)

(untitled) - Islam, M.; Shinde, G. P.; Hotha, S. (Chem. Sci., 2017)

(untitled) - Guberman, M.; Seeberger, P. H. (J. Am. Chem. Soc., 2019)

(untitled) - Kandasamy, J.; Hurevich, M.; Seeberger, P. H. (Chem. Commun., 2013)

(untitled) - Hahm, H. S.; Schlegel, M. K.; Hurevich, M.; Eller, S.; Schuhmacher, F.; Hofmann, J.; Pagel, K.; Seeberger, P. H. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Pardo-Vargas, A.; Delbianco, M.; Seeberger, P. H. (Curr. Opin. Chem. Biol., 2018)

(untitled) - Eller, S.; Collot, M.; Yin, J.; Hahm, H. S.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2013)

(untitled) - Yu, Y.; Kononov, A.; Delbianco, M.; Seeberger, P. H. (Chem. – Eur. J., 2018)